Redenção: uma cidade média do agronegócio na Amazônia? - SANTOS, Thamiris de Oliveira (Universidade Federal do Pará, 2021)
The town of Redenção, located in Southeastern Pará, is part of the Amazon frontier as a space for the expansion of capitalist activity, on the limits between the Amazon and the Brazilian Cerrado. The research whose results are presented in this dissertation focuses on understanding the historical-geographical formation of this urban nucleus’ centrality and its spatial manifestation. The methodological procedures adopted were: review of theoretical-conceptual literature on medium sized cities, agribusiness and its impacts on Brazilian urban spaces; review of historical-geographical literature on the sociospatial formation of Southeastern Pará and of the town of Redenção; primary and secondary data collection in federal, state and municipal government websites; and the application of formularies in commercial establishments in the town. The research concludes that, despite the importance of agribusiness and the resulting trade and services activities to the town of Redenção, the intraurban sociospatial inequality reveals the contradictions caused by an activity that concentrates wealth in the hands of a few agents; hence the importance of the public sector to the Municipality, not only in the creation of jobs, but also in the income transfer to a significant portion of the local poor population.